2010
DOI: 10.1183/09031936.00034409
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 in asthmatic patients, and its correlations with exacerbation, eosinophils and immunoglobulin E

Abstract: The chitinase-like protein YKL-40, which binds chitin but lacks chitinase activity, has been found to be either the cause or a biomarker for asthma. The aim of our study was to investigate whether serum YKL-40 levels are increased in Chinese patients with asthma and identify its correlation to acute exacerbation, total serum immunoglobulin (Ig)E, the percentage of peripheral blood eosinophils and lung function. We quantified serum YKL-40 levels, total IgE levels and peripheral blood eosinophil percentages in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
61
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 16 publications
12
61
3
2
Order By: Relevance
“…Serum YKL-40 levels and chitotriosidase activity have not previously been examined in parallel in patients with COPD and patients with asthma. The finding of increased serum YKL-40 in patients with asthma confirms previous observations (7,8,24,25). The higher levels in patients with severe asthma than in patients with mild asthma, along with the correlation between YKL-40 and reduced lung function, strengthen the association of serum YKL-40 with disease severity (7,8).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Serum YKL-40 levels and chitotriosidase activity have not previously been examined in parallel in patients with COPD and patients with asthma. The finding of increased serum YKL-40 in patients with asthma confirms previous observations (7,8,24,25). The higher levels in patients with severe asthma than in patients with mild asthma, along with the correlation between YKL-40 and reduced lung function, strengthen the association of serum YKL-40 with disease severity (7,8).…”
Section: Discussionsupporting
confidence: 79%
“…The higher levels in patients with severe asthma than in patients with mild asthma, along with the correlation between YKL-40 and reduced lung function, strengthen the association of serum YKL-40 with disease severity (7,8). The exact biological role of YKL-40 remains unclear, but it consistently correlates with airway obstruction in studies of patients with asthma (7,8,24). YKL-40 associates with measures of airway remodeling, such as bronchial wall thickness and subepithelial Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In asthma, increased serum levels and lung expression of YKL-40 are correlated with disease severity, airway remodeling, and decreased pulmonary function (17). Our previous study also showed that the elevated serum YKL-40 levels in asthmatics were correlated positively with total serum IgE levels and the percentage of peripheral blood eosinophils and correlated inversely with lung functions (18). Based on these findings, YKL-40 is believed to be involved in the pathogenesis of asthma and has attracted the attention of many groups during last few years.…”
mentioning
confidence: 76%
“…particularly during exacerbation (27). YKL-40 has been shown to be secreted by bronchial macrophages and epithelium particularly in people with severe asthma (9) and allergen-sensitized mice (14).…”
Section: Discussionmentioning
confidence: 99%